2007
DOI: 10.1007/s12055-007-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral internal thoracic artery harvesting; anatomical variations to be considered

Abstract: Introduction: Predictable intrathoracic course, anatomical proximity to heart and long-term patency has made Internal thoracic artery (ITA) a conduit of choice in coronary artery bypass grafting (CABG). Its frequent bilateral use has necessitated the need to have a comparative knowledge of surgical anatomy of ITA on both sides.Methods: A random study was conducted on 100 adult human cadavers. Sternocostal wall was removed and fixed in 10% formalin and dissected for detailed anatomy of ITA. All observations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Other subtypes due to different ITA branching patterns the collateral supply is at high risk for disruption. 13 In spite of small statistical sample in this review, we suggest that the key point in harvesting methods is to preserve the collaterals, trying to apply clips close to the artery and do not use excessive cauterization but rapid interrupted spark to cut the branches. Still, Skeletonization of one of ITA may be beneficial.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Other subtypes due to different ITA branching patterns the collateral supply is at high risk for disruption. 13 In spite of small statistical sample in this review, we suggest that the key point in harvesting methods is to preserve the collaterals, trying to apply clips close to the artery and do not use excessive cauterization but rapid interrupted spark to cut the branches. Still, Skeletonization of one of ITA may be beneficial.…”
Section: Resultsmentioning
confidence: 94%
“…Sternal circulation can be diminished with the harvesting leading to sternal dehiscence 13 especially after using both ITA. Diabetes mellitus, BMI more than 35, severe COPD, exposure to radiotherapy and immunosuppressant 14 consider as risk factors that contribute to the raising incidence of this complication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now a day's unilateral / bilateral pedicle, sequential or free graft of ITA will be used in CABG surgery because of long term patency and event free survival. Now studies have shown that skeletonised bilateral internal thoracic artery grafting can provide better event free survival than single internal thoracic artery grafting in selected group of patients [3]. In autologous breast reconstruction internal thoracic vessels are widely used as recipient vessels.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely utilized for coronary artery bypass grafting (CABG) surgery. The ITA’s anatomic characteristics, such as distinct intrathoracic course and anatomical vicinity with the heart [ 1 ], its long-term patency [ 1 - 4 ], the long-term survival rate [ 2 , 4 ] and post-operative quality of life [ 5 ] render it as an excellent arterial graft for myocardial revascularization.…”
Section: Introductionmentioning
confidence: 99%